Implementasi Pendidikan Kewirausahaan: Menciptakan Lulusan SMK Berbakat Pengusaha Unggul - Misbah, Muhammad; Susi, Susilawati (Candradimuka: Journal of Education, 2025)
Entrepreneurship is one of the programs held at SMK Nurul Hikmah 2 Bekasi. This study aims to describe the implementation of student entrepreneurship program management. This study uses a qualitative approach with a phenomenological type. Data collection is carried out by data triangulation, namely by 1) interviews. 2) observation. 3) documentation. The findings produced in this study are 1) Planning, namely (a) students must be provided with provisions in the form of entrepreneurial knowledge and skills; (b) skills provision is given to students to be able to run their own businesses (entrepreneurship) after graduation and so that they are not dependent on the world of work; (c) activities take place both in the school environment, activities outside such as in small businesses located not far from the school (d) activities last for 1 month each; (e) students who participate in this activity are students of class X and class XI and; (f) Class X students observe small business actors, students participate in entrepreneurship workshop activities with small business actors, and class XI students carry out entrepreneurial activities by first compiling a business proposal. 2) Organizing. (grouping). Students are divided into several groups and share tasks. 3) Actuating (Implementation). Students carry out activities for 2 months in each program. The three programs are: 1) business observation. 2) preparation of business proposals. 3) workshops. 4) Supervision.